2015
DOI: 10.1097/aog.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

A Proactive Approach to Neonates Born at 23 Weeks of Gestation

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As our definitions for periviability and viability are evolving, delivery in this time frame involves complex decision making for patients and providers [10,11]. The inherent morbidity and mortality to the periviable neonate are apparent [12,13]; however, the implications to maternal reproductive health, particularly related to classical cesarean delivery (CD), are important considerations and require thoughtful deliberation. Even if a classical CD can be avoided, a recent study has shown that periviable low transverse CDs are associated with an increased risk of uterine rupture in subsequent pregnancies compared to low transverse CD performed at term (1.8% versus 0.4%; OR 4.7, 95% CI 1.7–13.4, p = .004) [14].…”
Section: Discussionmentioning
confidence: 99%
“…As our definitions for periviability and viability are evolving, delivery in this time frame involves complex decision making for patients and providers [10,11]. The inherent morbidity and mortality to the periviable neonate are apparent [12,13]; however, the implications to maternal reproductive health, particularly related to classical cesarean delivery (CD), are important considerations and require thoughtful deliberation. Even if a classical CD can be avoided, a recent study has shown that periviable low transverse CDs are associated with an increased risk of uterine rupture in subsequent pregnancies compared to low transverse CD performed at term (1.8% versus 0.4%; OR 4.7, 95% CI 1.7–13.4, p = .004) [14].…”
Section: Discussionmentioning
confidence: 99%
“…11 Care practices aimed at reducing morbidity and mortality of extremely preterm neonates have demonstrated success. 9, 22 Our analysis was an attempt to quantify the relative contributions of prolonging gestation and improving survival when preterm birth occurs. The successes are noteworthy but the work must continue.…”
Section: Commentmentioning
confidence: 99%
“…Worldwide, survival among infants born very preterm varies by available resources for obstetric and neonatal care, and perceptions of viability. 1517 Preterm survival at the earliest gestational ages has improved dramatically in developed countries, where the limit of viability has extended to 22 to 23 weeks gestation; yet survival at these gestational ages in developing countries is rare. 15 Improvements in the survival of very preterm infants in developed countries are the result of a variety of factors including improved insurance coverage during pregnancy; advanced obstetric and antenatal care; and improved systems of risk-appropriate care, including resuscitation and stabilization of high-risk newborns.…”
Section: Introduction/backgroundmentioning
confidence: 99%